2011
DOI: 10.4038/slja.v19i1.2866
|View full text |Cite
|
Sign up to set email alerts
|

Severe Leptospirosis - A case series and review

Abstract: BackgroundThe purpose of this retrospective case review was to identify different patterns of clinical presentation of severe leptospirosis, and to find out any correlation between organ specific complication/s and outcome of the patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 3 publications
(2 reference statements)
0
6
0
Order By: Relevance
“…Previous studies performed in Sri Lanka, conducted in ICUs found a significantly high mortality rates of 65% 12 It was also demonstrated that mortality rate increased with higher number of system involvement. Renal involvement, hypotension and pulmonary involvement were noted to be the most frequent complications with central nervous system involvement associated with a poor overall prognosis.…”
Section: Leptospirosis In Intensive Care Settingsmentioning
confidence: 68%
See 1 more Smart Citation
“…Previous studies performed in Sri Lanka, conducted in ICUs found a significantly high mortality rates of 65% 12 It was also demonstrated that mortality rate increased with higher number of system involvement. Renal involvement, hypotension and pulmonary involvement were noted to be the most frequent complications with central nervous system involvement associated with a poor overall prognosis.…”
Section: Leptospirosis In Intensive Care Settingsmentioning
confidence: 68%
“…In a Sri Lankan context, as previously mentioned a study done in ICU did reveal significantly higher mortality rate(65%) with regard to probable leptospirosis. 12 It is important to delineate the causes for the above variation. It is possible that genetic and virulence or serotype related factors may contribute towards high mortality noted in both studies from Sri Lanka in comparison with similar studies from Asian, South American and European series.…”
Section: Discussionmentioning
confidence: 99%
“…This is similar to the nding of Weeratunga, Fernando [75] who showed the presence of MODs was independently associated with the mortality. In a similar manner, another study found that mortality is increased with increased the number of the dysfunctional systems and critical care management at three organ involvement stage would improve the outcome of the patients [96].…”
Section: Discussionmentioning
confidence: 69%
“…This is similar to another finding by Weeratunga et al who showed the presence of MODs was independently associated with the mortality. In a similar manner, another study found that mortality was increased with increased the number of the dysfunctional systems and critical care management at three organ involvement stage would improve the outcome of the patients (92).…”
Section: Discussionmentioning
confidence: 71%